Integrating Cultural Heritage into the Classroom: The Gambang Semarang as an Educational Resource - Raharjo, Eko; Arif Fiyanto; Irfanda Rizki Harmono Sejati; Andreas Inu Harimuti (Universitas Negeri Semarang, 2024)
This article explores the potential integration of cultural heritage, specifically Gambang Semarang traditional music, into formal education at schools and universities. As a local art form rich in historical and cultural values, Gambang Semarang holds significant potential as an innovative educational resource. This study aims to investigate various strategies for incorporating this traditional music into an Outcome-Based Education (OBE) curriculum, providing students with a holistic and relevant learning experience. Employing a qualitative approach, this study delves into the perspectives of teachers, students, and art practitioners regarding the implementation of Gambang Semarang as an educational tool